DECARBONIZATION AS ONE OF THE WAYS TO SOLVE THE PROBLEMS OF GLOBALIZATION - Alona Korohod (Agora International Journal of Economical Sciences (AIJES), 2023)
Half a century, globalization has been a driving force in the development of world economies. Besides positive effects, globalization has also caused negative consequences: accelerated climate change, degradation of natural resources, and increased emissions. That is why, in the last decade, the importance of climate and decarbonization policies has increasingly appeared on the world agenda. In addition, recent geopolitical events, including COVID-19, the Russian invasion of Ukraine, further emphasize the importance of green solutions for recovery and decarbonization of countries' economies. This article aims to highlight the importance of decarbonization policies and identify the possibility of solving environmental and energy problems caused by globalization. Through an analysis of existing literature and different countries' policies, the article identifies the potential of decarbonization policies to mitigate the negative impacts of globalization on the environment and energy sector. The findings suggest that the adoption of decarbonization policies can lead to a reduction in greenhouse gas emissions, improved energy efficiency, the development of renewable energy sources, and green jobs, ultimately contributing to a more sustainable and resilient global economy.
Keywords: 330